Conditioning parental factors for term birth weight at 3 400 m above sea level - Villamonte, Wilfredo (2015)
Objectives: To determine maternal and paternal factors that influence term birth weight at 3 400 m above sea level and to determine a socioeconomic profile. Design: Prospective descriptive study. Setting: National Hospital Adolfo Guevara Velazco, EsSalud, Cusco, Peru. Participants: Women with term normal single pregnancies. Interventions: In 200 women with term normal single pregnancies we determined conditioning maternal and paternal factors. Main outcome measures: Conditioning factors. Results: After redefining each variable parameters, statistical significance was observed for the following: a) father´s factors: age, education level, occupation, altitude of birth, permanency at altitude; b) mother: age, education level, occupation, altitude of birth, residence at altitude, iron supplements, family income, previous pregnancy, history of living children, height and placental weight. Conclusions: The sum of 28 maternal and paternal variables defined via the proposed profile was directly proportional to birth weight at 3 400 m above sea level.